2015
DOI: 10.1371/journal.pone.0116155
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Clonidine, Atenolol, Amlodipine and Dihydrochlorothiazide, but Not Enalapril, Impairs the Sexual Function in Male Spontaneously Hypertensive Rats

Abstract: This study was designed to investigate the impact of representative antihypertensive drugs of 5 classes on the sexual function in male spontaneously hypertensive rats (SHR) at doses that achieved similar blood pressure (BP) reduction. The experiment was performed in 6 groups of male SHR. The dose are 20 μg/kg/day for clonidine, 3 mg/kg/day for enalapril, 20 mg/kg/day for atenolol, 2 mg/kg/day for amlodipine, and 10 mg/kg/day for dihydrochlorothiazide. SHR were treated for 3 months, and then the penile erection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Also the effect of oral intubation of atenolol (T1), atenolol plus vitamin E (T2) and vitamin E (T3) on gonadosomatic index are clarified a significant (P<0.05) decrease in gonadosomatic index compared to other groups throughout the experiment. Our results show atenolol treatment did not affect the gonadosomatic index (GSI) significantly and this results reinforced with (Lin et al, 2015). A significant decrease in sperm aviability was detected in group T1 after 56 days of treatment with atenolol may be due to oxidative insult which effect on sperm DNA and male fertility and could be effect on spermatogenisis and steroid biosynthesis of Leydig cells (Sakr et al, 2013) or may be due to the effect of atenolol on concentration of testosterone (Khan et al, 2004) promote spermatogenesis and maintenance of sperm production (Pineda et al, 2003).…”
Section: Gonadosomatic Index (Gsi) and Sperm Viability (Live Sperms Psupporting
confidence: 80%
“…Also the effect of oral intubation of atenolol (T1), atenolol plus vitamin E (T2) and vitamin E (T3) on gonadosomatic index are clarified a significant (P<0.05) decrease in gonadosomatic index compared to other groups throughout the experiment. Our results show atenolol treatment did not affect the gonadosomatic index (GSI) significantly and this results reinforced with (Lin et al, 2015). A significant decrease in sperm aviability was detected in group T1 after 56 days of treatment with atenolol may be due to oxidative insult which effect on sperm DNA and male fertility and could be effect on spermatogenisis and steroid biosynthesis of Leydig cells (Sakr et al, 2013) or may be due to the effect of atenolol on concentration of testosterone (Khan et al, 2004) promote spermatogenesis and maintenance of sperm production (Pineda et al, 2003).…”
Section: Gonadosomatic Index (Gsi) and Sperm Viability (Live Sperms Psupporting
confidence: 80%
“…In men with metabolic syndrome, irbesartan was found to improve sexual desire, frequency of sexual contacts and erectile function—even when paired with hydrochlorothiazide 31. A study looking at the long-term treatment of male hypertensive rats with clonidine, atenolol, dihydrochlorothiazide and enalapril found that enalapril was the only agent to not impair sexual function 32. In a cross-over study comparing lisinopril and atenolol, both groups exhibited a decrease in sexual activity, with a more drastic decrease in men receiving atenolol.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Accordingly, the N/L-type CCB has a probability of less activation of the renin-angiotensin system [18]. Moreover, the administration of AML suppresses an inflammatory response by reducing the production of TNF-alpha, IL-1beta, and IL-6 [19], all of which are osteoclastogenic [20, 21]. Lin demonstrated that AML compared to the control group significantly increased the testosterone level in male SHR without affecting the levels of the follicle-stimulating and luteinizing hormone [21].…”
Section: Discussionmentioning
confidence: 99%